What's new in the new regionalism in the Americas? - Devlin, Robert (IDB-INTAL Buenos AiresBR, 2001)
Attempts to substantiate that Latin America's recent wave of regional integration is indeed a New Regionalism, quite different from the old, and hence merits a more comprehensive perspective than in the past.